PENGARUH PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE NUMBERED HEAD TOGETHER BERBANTUAN FLIPBOOK TERHADAP PEMAHAMAN KONSEP MATEMATIS PESERTA DIDIK KELAS XI SMA NEGERI 1 LEMBANG JAYA - Pratiwi, Natasya (Jurnal Edukasi dan Penelitian Matematika, 2025)
One of the most important abilities to have when learning mathematics is the ability to understand mathematical ideas. However, in class XI of SMA Negeri 1 Lembang Jaya, this ability is still low. The proposed learning model to overcome this problem is the Numbered Heads Together (NHT) type cooperative learning model. Class XI of SMAN 1 Lembang Jaya is the focus of this research which aims to determine the relative advantages of NHT and direct learning models.  This study used a quasi-experimental design with a non-equivalent control group with post-test only. Learners enrolled in the study were from classes XI F1 and XI F2 of SMAN 1 Lembang Jaya, which constituted the study population. Quizzes and tests with descriptive question formats were utilized as research tools, t-test was used to analyze the data, and the resulting P-value was 0.036. If the P-value < α = 0.05, then H0 is rejected. Class XI at SMAN 1 Lembang Jaya benefited more from using the NHT model than the direct learning model.Keywords– Flipbook, Cooperative Learning Model, Direct Learning Model, Numbered Heads Together, Mathematical Concept Understanding